2012
DOI: 10.1155/2012/732404
|View full text |Cite
|
Sign up to set email alerts
|

Antileukemic Potential ofMomordica charantiaSeed Extracts on Human Myeloid Leukemic HL60 Cells

Abstract: Momordica charantia (bitter gourd) has been used in the traditional system of medicine for the treatment of various diseases. Anticancer activity of M. charantia extracts has been demonstrated by numerous in vitro and in vivo studies. In the present study, we investigated the differentiation inducing potential of fractionated M. charantia seed extracts in human myeloid HL60 cells. We found that the HL60 cells treated with the fractionated seed extracts differentiated into granulocytic lineage as characterized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 41 publications
(52 reference statements)
0
10
1
Order By: Relevance
“…The findings of this study negate the report of Soundararajan et al (2012) which explained that M. charantia seed fractions did not exhibit any antiproliferative activity. However, Soundararajan et al (2012) reported that the differentiation-inducing fraction in M. charantia was non-proteinaceous in nature, showing that the differentiation-inducing factor of M. charantia is different from its antitumor factors.…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…The findings of this study negate the report of Soundararajan et al (2012) which explained that M. charantia seed fractions did not exhibit any antiproliferative activity. However, Soundararajan et al (2012) reported that the differentiation-inducing fraction in M. charantia was non-proteinaceous in nature, showing that the differentiation-inducing factor of M. charantia is different from its antitumor factors.…”
Section: Discussioncontrasting
confidence: 93%
“…However, Soundararajan et al (2012) reported that the differentiation-inducing fraction in M. charantia was non-proteinaceous in nature, showing that the differentiation-inducing factor of M. charantia is different from its antitumor factors. Thus, the present study for the first time describes the differentiation inducing action of the methanol leaf extract of M. charantia which can be further studied as an inducer of differentiation and regeneration of normal cell, either alone or combined with the suboptimal concentrations of other known inducers of differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…M. charantia induces cell death by activating the caspase-3 enzyme and increase the level of apoptogenic protein and the expression of Bax gene, which induces DNA fragmentation and nuclear condensation [58]. Treatment of fractionated seed extract of M. charantia in human myeloid HL60 cells induced the differentiation and can be used as therapy for leukemia [59]. Pitchakarn et al [60] reported that fresh bitter melon leaf extract significantly decreased the gene expression of MMP-2 and MMP-9 in a breast cancer cell line.…”
Section: Anti-cancer Activitymentioning
confidence: 99%
“…Some pharmacological and safety studies of this herb have been carried out 16,17 . In addition to hypoglycaemic activity, M.charantia has been shown to have antioxidant [18][19][20] , anti-tumour [21][22][23][24][25] , neuroprotective 26 , anti-inflammatory [27][28][29] and antimicrobial activity 30,31 . It has a resistance modifying effect for aminoglycosides against methicillin-resistant Staphylococcus aureus 32 .…”
Section: Introductionmentioning
confidence: 99%